Developmental plasticity of Arabidopsis hypocotyl is dependent on exocyst complex function - Janková Drdová, Edita; Klejchová, Martina; Janko, Karel; Hála, Michal; Soukupová, Hana; Cvrčková, Fatima; Žárský, Viktor (Journal of experimental botany, 2019)
The collet (root-hypocotyl junction) region is an important plant transition zone between soil and atmospheric environments. Despite its crucial importance for plant development, little is known about how this transition zone is specified. Here we document the involvement of the exocyst complex in this process. The exocyst, an octameric tethering complex, participates in secretion and membrane recycling and is central to numerous cellular and developmental processes, such as growth of root hairs, cell expansion, recycling of PIN auxin efflux carriers and many others. We show that dark-grown Arabidopsis mutants deficient in exocyst subunits can form a hair-bearing ectopic collet-like structure above the true collet, morphologically resembling the true collet but also retaining some characteristics of the hypocotyl. The penetrance of this phenotypic defect is significantly influenced by cultivation temperature and carbon source, and is related to a defect in auxin regulation. These observations provide new insights into the regulation of collet region formation and developmental plasticity of the hypocotyl.
Keywords: exocyst; Arabidopsis; etiolated hypocotyl; proteiny huseníčku; starch accumulation; collet; Arabidopsis thaliana; hypokotyl; Arabidopsis Proteins; root–hypocotyl junction; Hypocotyl; auxin